Beaten by Chartbeat?: An Experimental Study on the Effect of Real-Time Audience Analytics on Journalists' News Judgment. (11th March 2020) - Lamot, Kenza; Van Aelst, Peter
ABSTRACT: Traditionally, journalists had the autonomy to decide what is worthy enough to be considered news. However, the growing centrality of audience analytics in the news selection process warrants greater scrutiny in how these tools are likely to influence journalistic perceptions on which news stories the public is most interested in. Taking a quantitative approach, we conducted a survey-embedded experiment among political journalists in Belgium ( n  = 136). The journalists were asked to rank a set of five headlines from most to least prominent on a fictional homepage of a news outlet. Stories with positive analytics were genuinely ranked higher compared with stories in the control condition, whereas stories with negative analytics were ranked lower. Especially for soft news items, it seems that audience analytics can make a difference. However, for hard news, the effect was not significant. Furthermore, the effect of audience analytics remains limited compared with the impact of a traditional news value such as negativity. In this way, this study confirms, but also nuances, the impact of audience metrics.